Game theoretic approach for public multi‐mode transportation in smart cities. Issue 5 (20th April 2021) - Bin Hariz, Mohammed; Said, Dhaou; Mouftah, Hussein T.
Abstract: Here, a dynamic multi‐mode transportation model is developed in which the passenger, for his trip, can use one or a combination of the transportation forms such as a car, a bus or a bicycle. This model is based on the game theory concept‐based trip cost‐optimization and it is called game theory multi‐mode transportation. The proposed system is implemented through a realistic scenario in a specific city using the OMNET++ and the OpenStreetMap software tools. The results show that the average trip price and the average trip time are improved when using the proposed model.